Spatial distribution of species richness and endemism of Solanum (Solanaceae) in Mexico - Murillo-Pérez, Geraldine; Rodríguez, Aarón; Sánchez-Carbajal, Daniel; Ruiz-Sanchez, Eduardo; Carrillo-Reyes, Pablo; Munguía-Lino, Guadalupe (Phytotaxa, 2022)
The spatial distribution of the species richness is not aleatory. It responds to evolutionary, geographical, and climatic events, and it is important to establish biodiversity management and conservation priorities. The mountainous zones around the globe have been identified as centers of plant diversification. In Mexico, the Mexican Transition Zone (MTZ) which comprises the main mountainous chains is recognized as an area of high species richness and endemism. The genus Solanum (Solanaceae) includes 1228 accepted species distributed all over the world, but with centers of species richness and endemism in the neotropical mountains. Based on patterns observed in geographical distribution of Mexican biodiversity, we expect the MTZ to host the highest species richness and endemism of Solanum. Here, we evaluated the spatial distribution of the species richness and endemism of Solanum in Mexico. For that purpose, we used 10043 unique georeferenced records obtained from herbarium specimens, specimens cited in literature and electronic databases. Then, we quantified species richness and endemism using biogeographical regions and provinces, a grid-cell of 50 × 50 km, political division, vegetation types, elevational, latitudinal, as well as longitudinal gradients. In addition, we analyzed endemism through weighted endemism and corrected weighted endemism. In Mexico, there were 134 species of Solanum including 43 endemics. The species richness and endemism were concentrated along the MTZ, specifically in the Chiapas Highlands, Sierra Madre del Sur (SMS), and Transmexican Volcanic Belt (TVB). Eight cells containing 63.43% of the species were obtained in the grid-cell analysis. The species richness distribution assessment by vegetation type, elevation, and political division confirmed the MTZ as the richest region. Likewise, the endemism was found along the MTZ in the Sierra Madre Oriental, SMS, TVB as well as in Chihuahuan Desert. Complex geological and paleoclimatic history, irregular topography, current climate diversity, dispersal, and persistence influenced these patterns. Lastly, we confirmed the remarkable importance of the MTZ as a center of origin, diversification and endemism of Mexican plants, using one of the most representative genera in Mexico.